Organizaciones de pequeños productores, certificaciones y competitividad: experiencia reciente en Costa Rica - Díaz Porras, Rafael Antonio (2016)
Increasing private and public regulations to production processes with stringent requirements to participate in markets have led small and medium producers to face numerous crossroads to meet those requirements. This article investigates whether the application of environmental certifications has resulted in an improvement in the competitiveness of small and medium growers. The analysis focuses on the background of the certifications both at international and local levels, and approaches the real experiences of small producer organizations based on a survey conducted in 2015. This paper concludes th at the strategy of obtaining certifications has improved grower organizations positioning and, consequently, their stability in the value chain. Nevertheless, organizations and entities generating policies face important areas for improvement, such as costs and changes in production processes and cultural resistance to this type of initiatives